2020
DOI: 10.18280/jesa.530608
|View full text |Cite
|
Sign up to set email alerts
|

Proxy-Based Sliding Mode Vibration Control with an Adaptive Approximation Compensator for Euler-Bernoulli Smart Beams

Abstract: Proxy-based sliding mode control PSMC is an improved version of PID control that combines the features of PID and sliding mode control SMC with continuously dynamic behaviour. However, the stability of the control architecture maybe not well addressed. Consequently, this work is focused on modification of the original version of the proxy-based sliding mode control PSMC by adding an adaptive approximation compensator AAC term for vibration control of an Euler-Bernoulli beam. The role of the AAC term is to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This study can be extended to apply other recent control strategies for the elbowexoskeleton system. Accordingly, one can conduct a comparison study between the SMC and the suggested control schemes to show their effectiveness in trajectory tracking [41][42][43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…This study can be extended to apply other recent control strategies for the elbowexoskeleton system. Accordingly, one can conduct a comparison study between the SMC and the suggested control schemes to show their effectiveness in trajectory tracking [41][42][43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The Lyapunov theory is used as a basis for guaranteeing the stability of the proposed control law and the corresponding updating laws associated with unknown parameters. For unknown time-varying parameters, adaptive approximation control is used instead to comprise model-free techniques or so-called intelligent control [25][26][27][28][29][30][31][32][33][34]. On the other hand, robust control requires knowledge of limits of uncertainty.…”
Section: Introductionmentioning
confidence: 99%